ACE and ACE2 Gene Variants Are Associated With Severe Outcomes of COVID-19 in Men - Martínez-Gómez, Laura E.; Herrera-López, Brígida; Martinez-Armenta, Carlos; Ortega-Peña, Silvestre; Camacho-Rea, María del Carmen; Suarez-Ahedo, Carlos; Vázquez-Cárdenas, Paola; Vargas-Alarcón, Gilberto; Rojas-Velasco, Gustavo; Fragoso, José Manuel; Vidal-Vázquez, Patricia; Ramírez-Hinojosa, Juan P.; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 is responsible for the current COVID-19 pandemic, affecting more than 219 countries and causing the death of more than 5 million people worldwide. The genetic background represents a factor that predisposes the way the host responds to SARS-CoV-2 infection. In this sense, genetic variants of ACE and ACE2 could explain the observed interindividual variability to COVID-19 outcomes. In order to improve the understanding of how genetic variants of ACE and ACE2 are involved in the severity of COVID-19, we included a total of 481 individuals who showed clinical manifestations of COVID-19 and were diagnosed by RT-PCR. Genomic DNA was extracted from peripheral blood and saliva samples. ACE insertion/deletion polymorphism was evaluated by the HRM method; ACE SNP (rs4344) and ACE2 SNP’s (rs2285666 and rs2074192) were genotyped using TaqMan probes. We assessed the association of ACE and ACE2 polymorphisms with disease severity using logistic regression analysis adjusted by age, sex, hypertension, type 2 diabetes, and obesity. The severity of the illness in our study population was divided as 31% mild, 26% severe, and 43% critical illness; additionally, 18% of individuals died of whom 54% were males. Our results showed in the codominant model a contribution of ACE2 gene rs2285666 T/T genotype to critical outcome (OR=1.83; 95%CI=1.01-3.29; P=0.04) requiring oxygen supplementation (OR=1.76; 95%CI=1.01-3.04; P=0.04), in addition to a strong association of the T allele of this variant to develop critical illness in males (OR=1.81; 95%CI=1.10-2.98; P=0.02). We suggest that the T allele of rs2285666 represents a risk factor for severe and critical outcomes of COVID-19, especially for men, regardless of age, hypertension, obesity, and type 2 diabetes.